(untitled) (Педагогіка вищої та середньої школи, 2007)
Author proves that process of schooling of teachers-Ukrainian philologists have to build with paying attention to row of sociolinguistic factors, among their number functional co-relation between Russian and Ukrainian in modern linguistic situation. Future philologist must study bases o f sociolinguists. Educating work has to be turned to forming o f positive stereotyping image of Ukrainian.